2004
DOI: 10.1097/00043426-200411000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Ataxia in Pediatric Patients With Langerhans Cell Histiocytosis

Abstract: The pathogenetic mechanisms of the central nervous system (CNS) problems associated with Langerhans cell histiocytosis (LCH) are not well established. Effective treatment strategies for these CNS complications are not yet available, while diabetes insipidus, also associated with LCH, can be managed effectively. Three Japanese boys with LCH who developed cerebellar ataxia were evaluated. Similar pediatric cases from the literature are also discussed. All three patients initially developed multifocal LCH lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…However, it is possible that these incidences may become higher if the follow-up period of our series is much longer than the current median 5 years. In terms of ND disease, our previous analysis of patients with LCH-induced ND disease revealed that only half had CDI [19]. Thus, the six ND disease cases that were detected here in association with CDI do not account for all neurologically impaired cases in the cohorts of the JLSG-96/-02 studies [20].…”
Section: Discussionmentioning
confidence: 56%
“…However, it is possible that these incidences may become higher if the follow-up period of our series is much longer than the current median 5 years. In terms of ND disease, our previous analysis of patients with LCH-induced ND disease revealed that only half had CDI [19]. Thus, the six ND disease cases that were detected here in association with CDI do not account for all neurologically impaired cases in the cohorts of the JLSG-96/-02 studies [20].…”
Section: Discussionmentioning
confidence: 56%
“…Degenerative CNS disease developed in 3 patients, including 1 patient in the SS‐m group and 2 patients in the MS group. Details on these patients were published previously 14…”
Section: Resultsmentioning
confidence: 99%
“…LCH patients presenting with cerebellar ataxia have been rarely reported, and even then exclusively pediatric cases [8, 9, 10, 11, 12]. In those patients, cerebellar ataxia appeared with LCH progression after initial presentation of a skin or bone lesion.…”
Section: Discussionmentioning
confidence: 99%